PENYELESAIAN SENGKETA EKONOMI SYARIAH MELALUI BADAN ARBITRASE SYARIAH NASIONAL - Usammah Usammah (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2017)
In Indonesia, sharia arbitration was established in conjunction with the establishment of Bank Muamalat Indonesia (BMI) in 1992. The objective was to handle disputes between the customer and the first Sharia Bank. The Arbitration Institute is known as the Indonesian Arbitration Board of Muamalat (BAMUI) based on Decree No. Kep-392 / MUI / V / 1992. In 2003, several Banks or Sharia Business Units (UUSs) were born so that BAMUI was changed to the National Shariah Arbitration Board (Basyarnas). The amendment was based on Decree of MUI No. Kep-09 / MUI XII / 2003 dated December 24, 2003. However, the existence of Basyarnas can not simply be functioned. Must be underlined, the settlement through Basyarnas can be done if in the contract made a clause on the settlement of disputes through Arbriter.